Cognitive Aptitude and Motivational Commitment in the Educational Success of Students with and without Learning Difficulties - Oliveira Pereira, Fernando (2019)
The structure of mental activity and the consequent development of its components functionally affect the quality of the students’ performance. The aim of this research was to know the difference between some structural details of the psychological levels of the functionality of the students with and without learning difficulties. It is a predominantly quantitative and experimental study with independent variables such as age, school year, school retentions, cognitive aptitude and motivation to learn, and with dependent variables such as performance or school success. The sample of this research consisted of 550 students: 275 with and 275 without learning difficulties. The methodological instruments used were psychological interviews, sociodemographic questionnaires, record of the students' performance in the three periods of the last two school years and evaluation by teachers and parents of the students' abilities to learn and motivation to study. The results show that the components of the learning activity - cognitive aptitude, motivational commitment and educational success - present important differences within the framework of intercorrelations between components in the students with learning difficulties in comparison to the students without learning difficulties. In the first case, the consistency of the links between the various studied components is lower. The discussion of the data shows and concludes that the less strong connection between the components of academic performance, aptitude for learning and motivation to study, leads to a greater dispersion of the levels of psychic functioning of students with learning difficulties.